NEGATIVE TREND IN ASSOCIATION OF UROMODULIN WITH BLOOD PRESSURE IN PREHYPERTENSIVES AND UNTREATED HYPERTENSIVES WITH NORMAL KIDNEY FUNCTION. (June 2018) - Simicevic, L.; Josipovic, J.; Milicic, B.; Dapic, K.; Bozina, N.; Dika, Z.; Domislovic, V.; Fucek, M.; L.Gellineo,; Jelakovic, A.; Kos, J.; Rogic, D.; et al.
Abstract : Objective: Uromodulin and minor G allele UMOD gene rs13333226 have been associated with blood pressure (BP), hypertension (HT) and better renal function. Our aim was to analyze the association of uromodulin and the frequency of G allele with BP and kidney function in untreated subjects with a normal glomerular filtration rate (GFR). Design and method: From 894 participants of the ENAH follow up, a cohort group of 559 untreated subjects (men 55.8 %, cohort group mean age 38.6) with an eGFR > 60 ml/min/1.73m2 (CKD Epi equation) were enrolled into the study. Subjects were divided in three subgroups: optimal BP (OBP; N = 107), prehypertension (PHT; N = 145) and HT (N = 307). UMOD genotyping rs12917707polymorphism was performed by RT-PCR with the fluorescence-based TaqMan system, while urinary uromodulin levels were measured by Enzyme Linked Immunosorbent Assay (ELISA). Results: We failed to find difference in uromodulin levels among BP categories. However, a negative association of uromodulin with systolic BP (NS) and diastolic BP (r = 0.20; p = 0, 069) was observed in the entire group. No association between uromodulin and eGFR was noted. Uromodulin was found to be lower in women than men. The frequency of A and G alleles was 83.2% and 16.8%, respectively. No difference in the frequency of G allele was found among the BP categories. A trend of higher uromodulin was observed in homozygous for the G allele. No significant trend was observed between uromodulin and eGFR in the entire group. Conclusions: There is trend of negative association of uromodulin with BP in middle-aged untreated subjects with normal kidney function. We did not find an association of uromodulin with eGFR. A trend of a higher uromodulin urine concentration was observed in subjects with the G allele of UMOD rs13333226.